(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The author of the article attempts to analyze the current preschool education system of Uzbekistan, its main challenges, shortcomings and reforms. Moreover, this research will provide the study of the importance oflearning at early ages (3-5) and its impact on the future learning and personal development of children. The research highlights the analysis of domestic and foreign prospects of the studied issue. Namely, the researcher presents the view that developed countries pay more and more attention to boost the quality of pre school educational institutions, the efficiency of curriculum, and implementation of more social activities to enhance the development of children’s soft skills; however,this is not the case in developing countries such as Uzbekistan.